Alteration of HLA‐F and HLA I antigen expression in the tumor is associated with survival in patients with esophageal squamous cell carcinoma. Issue 1 (17th May 2012) - Zhang, X.; Lin, A.; Zhang, J.‐G.; Bao, W.‐G.; Xu, D.‐P.; Ruan, Y.‐Y.; Yan, W.‐H.
Abstract Alteration of human leukocyte antigen (HLA) expression, such as decreased HLA I (HLA‐A, ‐B and ‐C) antigens and elevated nonclassical HLA I antigens (HLA‐E, ‐F and ‐G), was reported to have an unfavorable prognosis in various cancers. In our study, HLA‐F expression in 105 primary esophageal squamous cell carcinoma (ESCC) lesions and 62 case‐matched adjacent normal tissues, and HLA I antigens among 68 cases were analyzed by immunohistochemistry. Data revealed that HLA‐F expression was observed in 58.1% (61/105) of the ESCC lesions and in 54.8% (34/62) of the normal esophageal tissues. Among the 62 case‐matched samples, HLA‐F expression (lesion vs. normal tissue) was upregulated, unchanged and downregulated in 13 (21.0%), 6 (9.6%) and 43 (69.4%) cases, respectively. Patients with HLA‐F positive had a worse survival than those with HLA‐F negative (p = 0.040). Patients with upregulated HLA‐F expression (lesion vs. normal tissue) had significantly worse survival than those with HLA‐F unchanged and downregulated (p = 0.010). Furthermore, decreased HLA I expression was observed in 41.2% (28/68) patients and was with worse prognosis in comparison to those with preserved HLA I expression (p = 0.001). Multivariate analysis using Cox's proportional hazards model revealed that upregulated HLA‐F expression (p = 0.026) and downregulated HLA I expression (p = 0.013) could be an independent unfavorable prognostic factor. In conclusion, our study provided the evidence that alteration of HLA I and HLA‐F antigen expression was associated with survival in patients with ESCC.